SistEX um sistema dinâmico para detectar a experiência do aluno - Possobom, Camila Cerezer (2014)
The widespread use of virtual learning environment (VLE) has great potential for the development of applications that meet needs in education. U -Learning environments the goal is to seek information related to the needs and preferences of users to create their context and present adaptations in its content to suit the user's profile, as in most traditional VLEs, such as Moodle, this process is not generally considered. Given the importance of a dynamic application that can continually adapt to the levels of students' knowledge, this dissertation proposes a module called SistEX (A Dynamic System for Detecting Student Experience). The adaptations in the environment used the Adaptive Hypermedia, and the type of information collected was the level of user knowledge, which were obtained through questionnaires applications. Furthermore, it was used and adapted the algorithm Q -Learning, from the intelligent tutoring system (ITS), to contribute to the user's learning process. As a result, the Software and user testing demonstrated that the environment SistEX worked satisfactorily, based on the assessments made by users who tested the module and its operation. The questionnaire was the System Usability Scale (SUS) on the module developed, which gave a result within a range considered good, which includes the objectives proposed in this work, even though some limitations and difficulties have been identified during development.